Combining dual-targeted liquid metal nanoparticles with autophagy activation and mild photothermal therapy to treat metastatic breast cancer and inhibit bone destruction. (February 2023) - Shen, Yaping; Zou, Yang; Bie, Binglin; Dong, Chanjuan; Lv, Yonggang
Abstract: Although mild photothermal therapy (mild-PTT) avoids treatment bottleneck of the traditional PTT, the application of mild-PTT in deep and internal tumors is severely restricted due to thermal resistance, limited irradiation area and penetration depth. In addition, bone resorption caused by tumor colonization in distal bone tissue exacerbates tumor progression. Here, a strategy was developed for the treatment of bone metastasis and alleviation of bone resorption, which was based on liquid metal (LM) nanoparticle to resist thermal resistance induced by mild-PTT via autophagy activation. Briefly, LM and autophagy activator (Curcumin, Cur) were loaded into zeolitic imidazolate framework-8 (ZIF-8), which was then functionalized with hyaluronic acid/alendronate (CLALN). CLALN exhibited good photothermal performance, drug release ability under acidic environment, specifical recognition and aggregation at bone metastasis sites. CLALN combined with mild-PPT dramatically inhibited tumor progress by inducing the impaired autophagy and reduced the expression of programmed cell death ligand 1 (PD-L1) protein triggered by mild-PTT, resisting thermal resistance and alleviating the immunosuppression. Besides, CLALN combined with mild-PPT effectively alleviated osteolysis compared with only CLALN or mild-PPT. Our experiments demonstrated that this multi-functional LM-based nanoparticle combined with autophagy activation provided a promising therapeutic strategy for bone metastasis treatment. Statement of significance: Due to the limited light penetration, photothermal therapy (PTT) has limited inhibitory effect on tumor cells colonized in the bone. In addition, nonspecific heat diffusion of PTT may accidentally burn normal tissues and damage peripheral blood vessels, which can block the accumulation of drugs in deep tumors. Here, a multifunctional liquid metal based mild-PTT delivery system is designed to inhibit tumor growth and bone resorption by modulating the bone microenvironment and activating autophagy "on demand". It can overcome the treatment bottleneck of traditional PTT and improve the treatment effect of mild-PTT by resisting photothermal resistance and immune suppression. In addition, it also exhibits favorable heat/acid-responsive drug release performance and can specifically target tumor cells at the site of bone metastases. Graphical abstract: Image, graphical abstract